Study of the True Clinical Progression of Autosomal Dominant Alport Syndrome in a European Population - Consolación Rosado; Elena Bueno; Carmen Felipe; Sebastián Valverde; Rogelio González-Sarmiento (Karger Publishers, 2015)
Background/Aims: Autosomal dominant Alport syndrome represents 5% of all Alport syndrome cases. This entity presents a different clinical expression from the recessive inheritance pattern and the X chromosome-linked pattern, because it is mild and it shows a late onset, which in many cases even goes unnoticed. Methods: We carried out a descriptive observational and retrospective clinical study on 19 patients from 5 families with a clinical diagnosis of autosomal dominant Alport Syndrome, and we analyzed the expression of the symptoms in the different families, comparing the results with what has been described in the literature. Results: Renal involvement appeared at a young age, with a progression towards end-stage chronic kidney disease at a median age of 31 years (20.5-36.5). Hearing involvement also appeared in early stages, at a median age of 28.5 years (7.5-62.5). Also, we observed ocular lenticonus-like injuries, which until now have only been described in other inheritance patterns. Conclusions: Our results suggest that dominant patterns are accompanied by a severe clinical expression that can be superimposed to the recessive and X chromosome-linked patterns, contrary to what has been classically stated. The high phenotypic variability observed in the families lead to the fact that many cases go unnoticed and the severest cases are erroneously diagnosed as recessive, which means that the real prevalence of dominant forms is probably higher than the current 5%.